Research on Metal-based High-temperature Superconductors and BCS Mechanism - Zhou, Yechen; Dong, Wei; Ye, Houde (Transactions on Environment, Energy and Earth Sciences, 2024)
Recently, high-temperature superconductors have had a wide range of applications in fields such as electric power transportation, medical imaging and diagnostics, electronic devices, and quantum computing. Therefore, this paper reviews the properties and mechanisms of copper-oxide, iron-based, nickel-based and hydrogen-based high-temperature superconductors. The results show that optimizing the copper-oxygen layer structure and regulating the interlayer coupling are effective methods to improve the performance of copper oxide high-temperature superconductors. This method can enhance the superconducting current, thus improving their superconducting properties. For iron-based high-temperature superconductors, the superconducting transition temperature and energy gap can be enhanced by doping rare earth elements or transition metal elements, and adjusting the topology of the Fermi surface to change the internal electronic structure of the material. The double-layer structure of nickel-based high-temperature superconductors is investigated by using tensor networks and other methods, which significantly increase the Tc of the material and solve the problems of difficult preparation by detecting the impurity effect and vortex state of the material. For hydrogen-based superconductors, chemical pre-pressurization and doping with alkali metal elements are mainly used to synthesize ternary hydrogen-based superconductors and hydrogen-minor superconductors. This can significantly increase the transition temperature of superconducting materials and reduces the pressure required for their preparation. Therefore, this study can improve the superconducting properties of these high-temperature superconductors and extend their applications in the fields of electric power transportation, medical imaging and diagnostics, electronic devices and quantum computing.